The unique rectus extraocular muscles of cetaceans: Homologies and possible functions. Issue 6 (19th January 2022) - Meshida, Keiko; Lin, Stephen; Domning, Daryl P.; Reidenberg, Joy S.; Wang, Paul C.; Gilland, Edwin
Abstract: Each rectus extraocular muscle in cetaceans divides into two portions: a massive palpebral belly that inserts into the deep surface of the eyelids and a smaller scleral belly that inserts onto the eyeball. While the cetacean palpebral insertions have long been recognized, their homologies and functions remain unclear. To compare cetacean rectus EOM insertions with the global and orbital rectus EOM insertions of other mammals we dissected orbital contents of 20 odontocete species, 2 mysticete species and 18 non‐cetacean species, both aquatic and terrestrial. Four cetacean species were also examined with magnetic resonance imaging (MRI). All four rectus muscles in cetaceans had well‐developed palpebral bellies and insertions. Adjacent palpebral bellies showed varying degrees of fusion, from near independence to near complete fusion. Fusion was most complete towards palpebral insertions and less towards origins. A medial moiety of the superior rectus palpebral belly is likely the levator palpebrae superioris. Smaller but still robust scleral insertions were present on all recti, with the medial rectus (MR) being significantly more muscular than the others. All non‐cetacean species examined had recti with distinct global and orbital insertions, the latter generally onto Tenon's capsule. Orbital insertions in pygmy hippopotamus and Florida manatee extended into the deep surfaces of the eyelids, hence qualifying as palpebral insertions. Our results suggest that rectus EOMs of mammals generally have both global and orbital insertions, and that palpebral bellies of cetaceans and other species are modified homologs of the orbital insertions. The presence of palpebral insertions in pygmy hippopotamus and absence in other cetartiodactyls suggests an intermediate condition between terrestrial cetartiodactyls and cetaceans. Palpebral insertions in Florida manatee and reports of their presence in some pinnipeds suggest parallel evolution in multiple aquatic lineages. Various functions of cetacean palpebral recti have been proposed, including eyelid dilators, protection during diving and thermogenesis for warming eye and brain. For further insight into their possible functions, we observed eye movements of captive bottlenose dolphins ( Tursiops truncatus ) at the U.S. National Aquarium. Our observations showed that in addition to rotation of the eyeball the entire surrounding palpebral region also moves during gaze changes. For example during upward gaze the globe not only rotates in supraduction but translates dorsally as well. It appears the rectus palpebral bellies are responsible for flexing the palpebral structures and thus also translating the globe, while the scleral insertions act directly for ocular rotation. Along with frequent non‐conjugate eye movements, the oculomotor mechanics and repertoire of cetaceans are thus quite distinctive. Summarily, axial displacement within the orbit is a major 'eye movement' in cetaceans, with protrusion and retraction mediated by well‐developed circular muscles and retractor bulbi respectively. Torsional eye movements driven by elaborate oblique EOMs are likewise significant. The roles of rectus EOMs for ocular rotation via their scleral insertions, especially the highly muscular MR, are for typical supra/infraductions and nasal/temporal ductions. The palpebral bellies accentuate these ductions by translating the globe and surrounding structures in the same direction. Abstract : Cross‐sectional MRI of a melon‐headed whale shows the complete fusion of the palpebral bellies of rectus extraocular muscles (red dots) except that of the medial rectus (MR) muscle (green dots). Our results suggest that the fused palpebral bellies are mainly responsible for dorso‐ventral and naso‐temporal translation of the eye which may be unique to cetaceans. Yellow dots show the scleral belly of MR.